(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Having access to food grains is the most important requirement for guaranteeing food security. The inability of the growing population to obtain food grains is the biggest problem facing the Indian government. After the green revolution, India’s domestic food grain production is largely self-sufficient, but it could not be enough to meet the country’s rising demand. This study’s primary goal is to determine the relationship between a country’s food security and agricultural productivity. The majority of the work is based on secondary data.